Pengaruh Media Sosial Terhadap Persepsi Diri dan Pembentukan Identitas Remaja - Pasenrigading, Andi Riola; Nur, Haerani; Daud, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of social media on self-perception and identity formation of adolescents through the literature review method. A total of 30 national and international scientific journals published in the period 2015–2025 were systematically analyzed to identify patterns, findings, and conclusions related to the phenomenon. The results of the study indicate that social media plays a major role in shaping adolescents’ self-perception through the process of social comparison, seeking external validation, and the need to conform to aesthetic standards and social norms formed in the digital space. In addition, social media is a place for exploring self-identity, but it can also trigger identity confusion due to social pressure and unrealistic expectations. These findings emphasize that intensive use of social media has the potential to have positive or negative impacts depending on the level of digital literacy and support from the adolescent’s social environment. This study recommends the importance of media education and the active role of parents and educational institutions in guiding adolescents to manage their self-identity in a healthy way in the digital era.